Inhibitory Effects of the Aerial Parts of Epimedium koreanum on TPA-Induced Inflammation and Promotion in Two-Stage Carcinogenesis in Mouse Skin - Ken Yasukawa; Sung-Kwon Ko; Wan-Kyunn Whang (Journal of Pharmacy and Nutrition Sciences, 2016)
Cancer prevention by supplements offers the most cost-effective long-term health strategy. Methanol extracts from the aerial parts of Epimediumkoreanum were previously found to inhibit 12-O-tetradecanoylphorbol-13-acetate (TPA)-induced inflammatory ear oedema and tumour promotion by TPA in the two-stage mouse skin carcinogenesis model. Four prenyl flavonol glycosides (14) were isolated from the active fraction of this extract, and were identified. The isolated compounds showed inhibitory activity against TPA-induced ear inflammatory ear oedema. The 50% inhibitory dose (ID50) of icariin (1), epimedin A (2), epimedin B (3) and epimedin C (4) for TPA-induced inflammation ranged from 114 to 255 nmol/ear, suggesting greater potency than indomethacin (ID50: 908 nmol/ear), an anti-inflammatory drug. Thus, the epimedium herb may be useful in cancer prevention.